Community Satisfaction of the Urban Flood Control System Improvement Project (UFCSI) - Mohammad Sofyan (Ilomata International Journal of Social Science, 2019)
The purpose of this study is to encourage ownership, responsibility and to develop stakeholders and policy makers for the river normalization program in the pre-construction, construction and post-construction stages. The use of the IPA method to measure community satisfaction in the quadrants on the Importance Performance Matrix map. The results of the study showed that the socialization from the Department of Water and Public Works, when the project was finished, was not in line with community expectations. Flood control projects that have been built, coordination with the contractor at the time of project implementation, socialization from the city government prior to project implementation, socialization from the city government when the project is finished, socialization from the river hall at the time before project implementation, socialization from the river hall at the time the project was completed, dissemination of information from the irrigation service prior to project implementation, and community involvement in project implementation. The process of land clearing, and the price agreement that has been reached. Improved land clearing, and price agreements that have been reached can be reconsidered because their impact on the benefits felt by the community is very small.